Nourishing millions: Stories of change in nutrition: Flyer - Gillespie, Stuart; Hodge, Judith; Yosef, Sivan; Pandya-Lorch, Rajul (International Food Policy Research Institute, 2016)
In recent years, the world has seen unprecedented attention and political commitment to addressing malnutrition. As nutrition rapidly rises on the global agenda, guidance is urgently needed on how to design, implement, and evaluate nutrition-enhancing policies and interventions. Nourishing Millions: Stories of Change in Nutrition brings together the most intriguing stories about improving nutrition from the past five decades. These stories provide insight into what works in nutrition, what does not, and the factors that contribute to success. The stories are rich and diverse, highlighting nutrition-specific programs and interventions; changes made in other sectors that have impacted nutrition; national-level progress in nutrition from developing countries; and how leadership in nutrition emerges and drives change. The result is a unique look at historical and emerging nutrition successes and challenges from around the world.